THE USE OF IMPORTANCE-PERFORMANCE ANALYSIS TO MEASURE THE SATISFACTION OF TRAVEL AGENCY FRANCHISEES - José M. Ramírez-Hurtado (RAE: Revista de Administração de Empresas, 2017)
This study contributes to the limited literature on the satisfaction of travel agency franchisees. Specifically, it aims to identify strengths and weaknesses of the system from the perspective of the franchisee. This study would enable franchisors to identify areas in which franchisees are less satisfied. If franchisees are satisfied with numerous aspects that influence the franchisor-franchisee relationship, the latter may have a high degree of loyalty towards their franchisors and this would benefit the entire network. This article uses a variant of the classic importance-performance model from Martilla and James (1977) and others (Ábalo, Varela, & Rial, 2006; Picón, Varela, & Braña, 2011). The results show that the attributes travel agency franchisees feel more dissatisfied with are: chain advertising, ongoing support from franchisors, the initial franchisor support, delivery from the franchisors, and training provided by franchisors.